Duties And Responsibilities Of Counselors At The Junior High School Ksatria Medan - Tarmizi, Muhammad; Fadillah, Siti Nazeli; Febrina, Mita Dwi; Siregar, Mayshe Baidannur (Yana Research, 2022)
This study aims to obtain information about the duties and responsibilities of counselors at Kesatria Private Junior High School Medan. The writing of this mini research was produced by interviewing the Guidance Counseling (BK) teachers in the school and collecting the data obtained. The results of this study are the authors get information about the duties and responsibilities of counseling counselors at SMPS Kesatria Medan.